Tantangan dan Solusi Penggunaan Bahasa Indonesia Yang Efektif Dalam Diskusi Akademik Untuk Meningkatkankan Kemampuan Berbahasa Mahasiswa Milenial - Ade Fransiska Br Barus; Asima Tiara Agnesia Pasaribu; Lili Tansliova (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study aims to identify challenges and solutions to the use of effective Indonesian in academic discussions on campus, as well as its implications for improving the language skills of millennial students. The use of effective Indonesian in academic discussions on campus is important for millennial students. However, there are challenges faced in practice, such as inadequate language skills, the influence of trends in the use of foreign languages, and a less supportive campus environment. This study aims to identify challenges and solutions in the effective use of Indonesian in academic discussions on campus. The results show that the main challenges faced are internal factors, such as the lack of Indonesian language skills, as well as external factors, such as the campus environment that tends to encourage the use of foreign languages.